Plumbagin ameliorates bile duct ligation-induced cholestatic liver injury in rats - Pin-Ho Pan (Biomedicine & Pharmacotherapy, 2022)
Plumbagin, a natural bicyclic naphthoquinone, has diverse pharmacological properties and biological benefits against a number of disorders, including liver disease. Though plumbagin’s hepatoprotective potential attracts attention, currently no experimental evidence exists on its effectiveness against cholestatic liver injury. The present study investigated its hepatoprotection in the rat model of extrahepatic cholestasis using Bile Duct Ligation (BDL). We found that daily plumbagin supplementation protected the liver from cholestatic damage. Hepatoprotective actions of plumbagin were accompanied by reduction of Transforming Growth Factor β1 (TGF-β1)/Smad, High Mobility Group Box-1 (HMGB1)/Toll-Like Receptor-4 (TLR4), Hypoxia-Inducible Factor-1α (HIF-1α), Aryl Hydrocarbon Receptor (AhR), Heat Shock Protein 90 (HSP90), caveolin-1, NF-κB/AP-1, Dynamin Related Protein-1 (Drp1), malondialdehyde level, Interleukin-1β (IL-1β), p62/SQSTM1, and caspase 3 as well as increase of Farnesoid X Receptor (FXR), bile acid efflux transporters, glutathione, LC3-II, Beclin1, and nuclear NF-E2-Related Factor-2 (Nrf2) and Transcription Factor EB (TFEB). The activation of nuclear Nrf2 caused by plumbagin correlated well with the improvement in bile acid retention, liver histology, serum biochemical, ductular reaction, mitochondrial dysfunction, oxidative stress, inflammation, apoptosis, impaired autophagy, and fibrosis, involving interplay of multiple intracellular signaling pathways. Plumbagin is likely a candidate drug to protect the liver from cholestatic damages. Despite the promising findings from this study, translational implication of plumbagin on cholestatic liver injury warrants further investigation.